A Mobile Game-Based Application for Learning Collective Nouns of Animals: Nounimals - BAHARODDIN, NUR ALYA BATRISYIA; CHE DALIM, CHE SAMIHAH (Applied Information Technology And Computer Science, 2025)
Game-based learning enhances engagement by combining educationalcontent with interactive play. Traditional methods of teachingcollective nouns for animals often lack interactivity, and existing appswith static visuals and text-based quizzes make it difficult for primaryschool students to learn this knowledge. Hence, Nounimals is a mobileapplication that uses game-based learning technology has beendeveloped by using a Multimedia Mobile Content Developmentmethodology. The app targets primary school students, offering 2Dvisualizations, gamified quizzes, and real-time feedback to makelearning collective nouns more engaging. The System Usability Scale(SUS) was used to evaluate user acceptance, resulting in a positiveusability score of 71.5, which is above the average benchmark of 68 andindicates good usability and user satisfaction. Thus, Nounimals aresuitable to be implemented in learning collective nouns of animals isexpected.